Empires Old, New, Reincarnated and Imaginary: Economic Build-ups in Eurasia, China and Russia in Afghanistan Naval Build-ups in the South China Sea Region – Their Forecasted Outcomes - Jones, David Arthur (Rethinking Asia in World Politics, 2023)
Maritime friction among powers, great and small, has escalated in the “Near Seas” region, including East China, Yellow, and South China Seas, largely because China has militarized that region by constructing artificial islands, and then fortifying them. United States warships repeatedly have conducted “Freedom of Navigation Operations” (FOPs) in the region, as have British, Indian, and Japanese warships, with France joining that list in early 2021 also. At the same time, China’s “Belt and Road Initiative” streams economically across Eurasia, with rising debt. This paper will address the objectives of China, the West, and neighbouring Asian countries in terms of increasing, decreasing, or replacing tensions in the region, as “empires” old, new, reincarnated and imaginary converge to participate in this fray. Inevitably, risk prevails, opportunities do also, as once-proud empires such as Britain, France, Russia, and Japan join in to confound if not deter China in its transparent effort as a rising power to control shipping and land transportation in this strategic but fragile corridor that connects Europe and the Middle East with Asia, vital to transporting raw materials, particularly energy, Eastward, and finished products, especially electronics and solar panels, Westward. Crucial issues emerging at a critical time require immediate but careful rethinking of Asia in world politics. Although a pandemic has altered and delayed the course of trade in 2020 and 2021, this may be both blessing and curse, a blessing in the sense that emerging power houses in Asia as well as Oceana have endeavoured to commit more resources toward augmenting the traditional Western powers, motivating them to become stronger Allies of the West. On the other hand, a curse, to the extent the opportunity for conflict increases as it has unfolded in Afghanistan over the summer of 2021. Perhaps this will inspire a rapprochement with China and instil in China a realistic expectation of achieving economic growth in moderation over a gradual time in contrast to a growth spurt in the short term that would lead to conflict and set China back much as Japanese aggression before 1945 led to warfare ending in Japan’s defeat and Allied victory. A desired outcome such as this may be unlikely, however, given China’s reported inroads into Afghanistan, rising threats to Taiwan.